PENGARUH MINAT MAHASISWA, ANTUSIASME, DAN PENGETAHUAN AKUNTANSI DIGITAL TERHADAP PEMANFAATAN TEKNOLOGI AKUNTANSI DIGITAL PADA MAHASISWA USI - Shahnaz Dwi Mulyana; Ade Manggala Hardianto; Ali Muhammad (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
Studi This study examines the influence of students' interest, enthusiasm, and knowledge of digital accounting on the utilization of digital accounting technology among former USI students. This research was motivated by the increasing need for digital competency in accounting along with technological advances. The quantitative approach used a survey method, with 100 respondents obtained through a saturated sampling technique. Data analysis was conducted using multiple linear regression with the help of SPSS version 25. The study findings indicate that students' interest, enthusiasm, and knowledge of digital accounting each have a positive and significant impact—both individually and collectively—on the utilization of digital accounting technology. These results emphasize the importance of strengthening students' digital literacy to effectively adapt to technological developments in the accounting profession. Keywords: Interest, Enthusiasm, Digital Accounting Knowledge, Digital Accounting Technology, USI Students.